A Time-Domain Fingerprint for BOC(m, n) Signals. (25th July 2007) - Muth Muth, B. B.; Oonincx Oonincx, P. P.; Tiberius Tiberius, C. C.
Abstract : Binary offset carrier (BOC) describes a class of spread-spectrum modulations recently introduced for the next generation of global navigation satellite systems (GNSSs). The design strategies of these BOC signals have so far focused on the spectral properties of these signals. In this paper, we present a time-domain fingerprint for each BOC signal given by a unique histogram of counted time elapses between phase jumps in the signal. This feature can be used for classification and identification of BOC-modulated signals with unknown parameters.